Peran Pendidikan Kewarganegaraan dalam Meningkatkan Kesadaran Hukum Warga Negara - Sartika Novriani; Syamzaimar Syamzaimar (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
This study aims to examine the role of Civic Education (PKn) in improving citizens’ legal awareness, especially among elementary school students. This research is motivated by the low level of legal awareness in society, which is reflected in various violations of existing rules and norms. The method used in this study is a qualitative approach with a descriptive design. Data collection was carried out through observation, interviews, and documentation of the implementation of Civic Education learning in elementary schools. The data obtained were analyzed using an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of discussion methods, case studies, and problem-based learning can improve students’ understanding, attitudes, and behavior in obeying the law. The discussion method helps students develop critical thinking skills and communication abilities, while the case study method makes it easier for students to understand the application of law in everyday life. In addition, problem-based learning has proven effective in training students’ abilities to solve problems and make decisions based on legal values. The success of the learning process is also influenced by teacher competence, a supportive school environment, and students active participation during learning activities. Therefore, Civic Education has an important role in shaping character and instilling a culture of legal awareness from an early age in order to create disciplined, responsible, and law-abiding citizens.